2016
DOI: 10.3917/cris.2301.0005
|View full text |Cite
|
Sign up to set email alerts
|

Les causes de la disparition des petits commerces (1945-2015)

Abstract: Terme néerlandais désignant un alignement de grands commerces sur les nationales aux entrées de villes. 4 Les données de Locatus relatives aux rues commerçantes sont mises à jour annuellement, celles relatives au commerce dispersé tous les deux ans. Ces données très utiles sont présentées et critiquées dans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
1
12
0
11
Order By: Relevance
“…For the period 1979-1988, our results confirm the work of Delobez and Péron (1991) which showed that city centres lost their retail monopoly in the 1980s, but maintained their supremacy over suburban and outlying areas. This situation did not persist into the following periods: from the beginning of the 2000s, the retail decline of city centres reported by Razemon (2016), Grimmeau and Wayens (2016) for Belgium, by Portas (2011) in England, or by various authors (Arata, 2012;Tsujii 2013;Yakushiji & Takahashi, 2013) and national surveys from the Ministry of Economy, Trade and Industry (METI) in Japan, is confirmed here.…”
Section: Variables With Unexpected Explanatory Behavioursupporting
confidence: 55%
See 2 more Smart Citations
“…For the period 1979-1988, our results confirm the work of Delobez and Péron (1991) which showed that city centres lost their retail monopoly in the 1980s, but maintained their supremacy over suburban and outlying areas. This situation did not persist into the following periods: from the beginning of the 2000s, the retail decline of city centres reported by Razemon (2016), Grimmeau and Wayens (2016) for Belgium, by Portas (2011) in England, or by various authors (Arata, 2012;Tsujii 2013;Yakushiji & Takahashi, 2013) and national surveys from the Ministry of Economy, Trade and Industry (METI) in Japan, is confirmed here.…”
Section: Variables With Unexpected Explanatory Behavioursupporting
confidence: 55%
“…In Belgium for instance, the number of small businesses fell from 370,000 in 1947 to 191,000 in 2015, a drop of 48 %. In terms of shopping space, small businesses are now playing a minor role in retail activity, as they represented less than 49 % of the total retailing surface area in 2014, compared with more than 59 % in 2007 (Grimmeau & Wayens, 2016). These trends are similar to those found internationally, although the intensity and pace of change may vary (Portas, 2011).…”
Section: -Retail Decline and Urban Change: An International Literatumentioning
confidence: 89%
See 1 more Smart Citation
“…Retail trade in Brussels: reconciling the city with a changing sector Brussels Studies , Notes de synthèse help shopkeepers move to more profitable locations [Grimmeau and Wayens, 2016], which are activities recognised as good practice in commercial revitalisation [Westvlaams Ekonomisch Studiebureau, 2015].…”
Section: Public Management Of Retail Tradementioning
confidence: 99%
“…L'apparition des friches commerciales devient importante ; une expression désigne ces bâtiments abandonnés : les dead malls. En Belgique, les cellules vacantes se sont multipliées depuis la fin de la Seconde Guerre mondiale, provoquant des situations de crise sociale et urbaine (Grimmeau et Wayens, 2016).…”
unclassified